Total C-21 Steroidal Glycosides From Baishouwu Ameliorate Hepatic and Renal Fibrosis by Regulating IL-1β/MyD88 Inflammation Signaling - Qin, Tingting; Wang, Mingliang; Zhang, Ting; Wang, Yingyu; Zhang, Yunyun; Hasnat, Muhammad; Zhuang, Zirui; Ding, Yongfang; Peng, Yunru (Frontiers in Pharmacology, 2021)
Fibrosis is a worldwide public health problem, which typically results from chronic diseases and often leads to organ malfunction. Chronic inflammation has been suggested to be the major trigger for fibrogenesis, yet mechanisms by which inflammatory signals drive fibrogenesis have not been fully elucidated. Total C-21 steroidal glycosides (TCSG) from Baishouwu are the main active components of the root of Cynanchum auriculatum Royle ex Wight, which exert hepatoprotective and anti-inflammation properties. In this study, we established a mouse model with the coexistence of hepatic and renal fibrosis and aimed to investigate the effects of TCSG from Baishouwu on fibrosis and explored the potential mechanisms. The results of biochemical and pathological examinations showed that TCSG from Baishouwu improved liver and kidney function and alleviated hepatic and renal fibrosis by reducing collagen and extracellular matrix deposition in bile duct ligation & unilateral ureteral occlusion (BDL&UUO) mice. According to network pharmacology analysis, the mechanisms underlying the effects of TCSG from Baishouwu on hepatic and renal fibrosis were associated with inflammatory response pathways, including “Signaling by interleukins”, “MAP kinase activation”, “MyD88 cascade initiated on plasma membrane”, and “Interleukin-1 family signaling”. Regression analysis and western blot results revealed that IL-1β/MyD88 inflammation signaling played an essential role in the anti-fibrotic effects of TCSG from Baishouwu. Further data displayed that TCSG from Baishouwu affected inflammatory response and extracellular matrix deposition via suppressing the activation of p38 MAPK/JNK and NF-κB p65 signaling cascades both in the liver and kidney of BDL&UUO mice. Thus, our findings suggest TCSG from Baishouwu as a natural regimen against hepatic and renal fibrosis and provide direct evidence that IL-1β/MyD88 signaling crucially contributes to hepatic and renal fibrosis and modulates liver-kidney crosstalk by maintaining tight control over inflammatory responses.